Culture and Entrepreneurial Orientation in Generation Z with Gender as a Mediating Variable - Ade Octavia; Zulfanetti Zulfanetti; Yayuk Sriayudha (University of Merdeka Malang, 2023)
Entrepreneurial orientation should develop as an integral part of strengthening entrepreneurial character. Generation Z, with different gender and culture, has distinct characteristics in terms of entrepreneurship. This study aims to analyze the following: (1) How culture and gender influence entrepreneurial orientation in the group of people who belong to Generation Z and (2) How gender can mediate the influence of culture and entrepreneurial orientation in Generation Z. The population of this study consists of the age group included in Generation Z, with a research sample of 200 respondents. This study used a probability sampling technique for data collection, using questionnaires as research tools. Data were analyzed using the Structural Equation Model (SEM/PLS). The results of this study expected to contribute to the theoretical implications for other researchers in related fields. The research findings show that there is an influence of culture and gender on entrepreneurial orientation. However, there is no influence of culture on gender. In addition, gender variables cannot mediate the relationship between culture and entrepreneurial orientation.